Penggunaan Media Pembelajaran Gambar untuk Pembelajaran Bahasa Indonesia Materi Puisi Kelas VII MTS Muhammadiyah 22 Padangsidimpuan - Devinna Riskiana Aritonang; Hanifah Parapat (jurnalalfa, 2025)
This study aims to determine the effectiveness of the use of picture learning media in improving students' understanding of poetry material in Indonesian subjects in grade VII MTs Muhammadiyah 22 Padangsidimpuan. This research uses the Classroom Action Research (CAR) method with two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were 30 grade VII students consisting of 15 male students and 15 female students. Data collection techniques include tests, observations, and questionnaires. The results of the study showed a significant improvement in student understanding. In the pre-test, the average score of students was 55, while after the application of image media in the first cycle, the average score increased to 70, and in the second cycle, the average score reached 85 with 90% of students passing the KKM. In addition, 80% of students responded positively to the use of image media, which showed an increase in students' interest and involvement in learning poetry. Based on these results, it can be concluded that image media is effective in increasing students' understanding and interest in poetry material in grade VII MTs Muhammadiyah 22 Padangsidimpuan.